Martínez Gallego, Francesc-Andreu. Samuel Ros, del humor nuevo a la camisa vieja (1905-1945) Madrid: Verbum, 2019 - López Viñas, Maila (Anales de Literatura Española, 2020)
Reseña de la publicación: Martínez Gallego, Francesc-Andreu. Samuel Ros, del humor nuevo a la camisa vieja (1905-1945) Madrid: Verbum, 2019, ISBN:9788490749128, 348 pp.